2006
DOI: 10.1111/j.1600-6143.2006.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Zygomycosis in Solid Organ Transplant Recipients in a Tertiary Transplant Center and Review of the Literature

Abstract: Zygomycetes are ubiquitous fungi that can cause invasive disease associated with high mortality. We report 10 solid organ transplant recipients with zygomycosis (incidence 2 per 1000) and reviewed 106 cases in the English-language literature. These included renal (n = 73), heart (n = 16), lung (n = 4), heart/lung (n = 2), liver (n = 19) and kidney/pancreas (n = 2) transplant recipients. All patients were receiving immunosuppression and the vast majority steroids. The clinical presentation included rhino-sino-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
257
4
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(272 citation statements)
references
References 91 publications
(121 reference statements)
4
257
4
7
Order By: Relevance
“…In another study, the lowest mortality rate 1 was reported in cutaneous mucormycosis (16%), rhinocerebral (67%), pulmonary (83%), gastrointestinal, and the disseminated form was associated with 100% mortality rate. 1 Einollahi and associates reported that rhinocerebral type was the most-common form of disease, followed by pulmonary in kidney transplant recipients. The overall mortality rate was 52%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, the lowest mortality rate 1 was reported in cutaneous mucormycosis (16%), rhinocerebral (67%), pulmonary (83%), gastrointestinal, and the disseminated form was associated with 100% mortality rate. 1 Einollahi and associates reported that rhinocerebral type was the most-common form of disease, followed by pulmonary in kidney transplant recipients. The overall mortality rate was 52%.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[7][8][9][10] A fungal stain (eg, Gomori methenamine silver) also is helpful if the fungus is not easily found. 1,9,11 In immunocompromised patients, these pathologic changes are usually associated with minimal inflammatory response. 9,11,12 Patients are usually treated with amphotericin B deoxycholate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucormycosis can be divided into at least six clinical categories: rhino-orbital-cerebral, pulmonary, cutaneous, gastro-intestinal, disseminated, and miscellaneous. Rhino-orbital-cerebral is the most common form of infection in patients with DKA, whilst pulmonary mucormycosis is seen in leukemic patients who are receiving chemotherapy and in patients undergoing (HSCT) [8][9][10]. Rhino-orbital-cerebral Mucormycosis occur in patients with diabetes, and rhizopus is the predominant pathogen, with the incidence of 90% of rhinoorbital-cerebral infections [1].…”
Section: Discussionmentioning
confidence: 99%